ANALYSIS OF PHYSICAL CONDITIONS OF DEGREES ATLET AT UNESA - YOGA, URI PRATAMA; Kafrawi, Fatkur Rohman (Jurnal Kesehatan Olahraga, 2019)
Abstract The physical condition of SME athletes fighting degrees at UNESA in each match is easy to experience fatigue, especially in the final round, such as running out of breath, swinging blows, and kicks under the belt. The purpose of this study was to determine the level of physical condition of athletes fighting degrees at UNESA. The target of this study was 8 UKM athletes fighting for UNESA degrees. The research was conducted around GOR BIMA and the Oentoeng Poedjadi athletic field in Surabaya State University. The research instruments used in this study were 30m Running Test to measure speed,test Shuttle Run 40m to measure agility,Test Sit-Up 30-secondto measure abdominal muscle strength,Test Sit and Reach to measure flexibility,Test Vertical Jump to measure explosive power leg muscles,Test Push-Up 1 minute to measure the endurance of arm muscles, and Multistage Fitness Test to measure the endurance of the heart and breathing. The results of a series of tests on the physical condition of UNESA combat athletes compared with the physical condition data of JATIM PON athletes showed that athletes with, tests Shutle Run UNESA degree fighters have an average of 14.02